2013
DOI: 10.1080/13607863.2013.788996
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the functional capacity on subjective well-being and quality of life of patients with silicosis

Abstract: The SWB and QOL of patients with silicosis are still relatively low and their health status needs improvement. At the same time, longer distances walked by patients suggest more positive influences on their SWB and QOL. It indicates that when the 6MWT cooperates with SWB and QOL, it may be able to get more accurate evaluation results of patients' survival status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
17
1
2
Order By: Relevance
“…BASDAI addresses disease activity which definitely affects quality of life, thereby, it is reasonable to draw such a conclusion. The conclusion is highly consistent with Bing Han’s research indicating functional capacity as predictor of psychological health [40], as well as the study of Geertzen which concluded that the influence on SWB was less when patients were physically independent [41]. Based on the findings of the present study, positive attitudes towards therapy prospect leads to higher well‑being of the patients with AS.…”
Section: Discussionsupporting
confidence: 92%
“…BASDAI addresses disease activity which definitely affects quality of life, thereby, it is reasonable to draw such a conclusion. The conclusion is highly consistent with Bing Han’s research indicating functional capacity as predictor of psychological health [40], as well as the study of Geertzen which concluded that the influence on SWB was less when patients were physically independent [41]. Based on the findings of the present study, positive attitudes towards therapy prospect leads to higher well‑being of the patients with AS.…”
Section: Discussionsupporting
confidence: 92%
“…Two-sided χ 2 tests and Student’s t-tests were used to evaluate distribution differences in demographic characteristics as well as in environmental exposures between the cases and controls. Logistic regression analyses with adjustment for age, gender, silica dust exposure years and smoking status were employed to evaluate associations between CPM and CPSF6 genetic variants and the development of silicosis and to estimate ORs and 95% CIs.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the quality of life of these patients is impaired; however, few studies have evaluated the impact of the disease on the quality of life of patients with silicosis. [13][14][15] There is no specific health questionnaire for this disease. A recent study investigated the impact of silicosis on quality of life of Chinese patients by George's Respiratory Questionnaire; the study sample presented a relatively moderate impact on the respirationrelated quality of life.…”
mentioning
confidence: 98%